2015
DOI: 10.1097/nrl.0000000000000040
|View full text |Cite
|
Sign up to set email alerts
|

Which Comorbidities and Complications Predict Ischemic Stroke Recovery and Length of Stay?

Abstract: Greater age and higher National Institute of Health Stroke Scale at admission were associated with both higher disability and longer LOS. Congestive heart failure, CRF, presence of arrhythmias, and development of acute renal failure were associated with greater LOS. The development of urinary tract infection caused higher disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 15 publications
2
26
0
7
Order By: Relevance
“…Seven studies were considered to be of good quality and one of fair quality. The eight studies provided data on 12,325,652 patients (range 897 to 7,068,334) from four countries (five from the US [ 20 , 22 24 , 26 ], and one each from China [ 21 ], Greece [ 25 ] and Romania [ 19 ]). The US studies overwhelmingly had the largest sample sizes, with a total of 12,319,724 patients representing 99.9% of all included patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven studies were considered to be of good quality and one of fair quality. The eight studies provided data on 12,325,652 patients (range 897 to 7,068,334) from four countries (five from the US [ 20 , 22 24 , 26 ], and one each from China [ 21 ], Greece [ 25 ] and Romania [ 19 ]). The US studies overwhelmingly had the largest sample sizes, with a total of 12,319,724 patients representing 99.9% of all included patients.…”
Section: Resultsmentioning
confidence: 99%
“…Although there are some differences in the grading of AKI severity between these classifications, both define the absolute incidence of AKI as an increase in serum creatinine > 150%. Stroke was determined using ICD coding in four studies [ 22 24 , 26 ]. Three studies utilized the World Health Organization (WHO) definition of stroke [ 27 ] and extracted clinical data from medical records prospectively [ 21 , 25 ] or retrospectively [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The length of hospitalization and in-hospital mortality was significantly longer in patients with haemorrhagic stroke than patients with ischaemic one. The recent study of Mohamed et al [28] showed that presence of CKD was associated with longer length of stay, which is the most predictive factor in determining in-patient costs.…”
Section: Discussionmentioning
confidence: 99%